The Development Of Learning Media Based On Kine Master Application For Pramuka Pionering Rope Training Raft RaiserAt Mts Negeri Dharmasraya - Muhammad Sukron; Alchonity Harika Fitri; Tomi Sugara (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2024)
This research was conducted by scout members who performed the scout pionering rope skill technique poorly. In carrying out the Scout Pionering Rope Skills Technique, making knots and ties in the scouts. Such as base knots, anchor knots, cross knots, dead knots, live knots, tripod ties, canal ties, cross ties and cross ties. The scout members also took a long time to do the scout pionering rope technique. The type of research is research and development, namely using the ADDIE development model which consists of an analysis stage, the analysis stage includes material analysis, analysis of student needs, and analysis of student characteristics. Design stage The design stage is designed for learning media based on the kine master application, namely instrument design and framework design. The development stage is a validation test. Implementation stage The implementation stage is carried out practicality and effectiveness. The evaluation stage is carried out at each stage starting from analysis, design, develop, and implementation. The results of the validation assessment of learning media based on the kine master application in the validation test by three experts have an average score of 80% language validation, 87.2% media validation, and 85% material validation included in the valid category, meaning that the learning media based on the kine master application is in accordance with the language, media and learning materials, the practicality test with an average score of 90% is categorized as very practical this means that the Kine Master application-based learning media can be used easily for the learning process, while the effectiveness of the Kine Master application-based learning media with a score of 70% is categorized as very effective, meaning that the application can improve the results of the Scout Rope Training.